Generative AI text summarization performance analysis prospects (Моделювання, керування та інформаційні технології, 2025)
AI investment world trends analysis in scope based on venture investments timeline by domain visualization and researches proves that not all AI-agent development projects are successful. The current paper describes an AI-agent performance analysis approach based on LLM-specific metrics and scenario-specific metrics. The AI-agent for highlights generation is in focus as an object of performance analysis.